Analysis of The Influence of the 7p Marketing Mix on Consumer Loyalty Shipping Services Company - Nengsih, Suriya; Bachri, Naufal; Edyansyah, T; Asbar, Yuli (Universitas Mercu Buana, 2024)
This study aims to determine and analyze the effect of the 7p marketing mix on consumer loyalty at the delivery service company (JNE) in Lhokseumawe city and to find out which JNE service factor has the most dominant effect on consumer loyalty at the JNE delivery service company in Lhokseumawe city. The object of this research is consumers who have used or are using JNE shipping services. The sample used amounted to 100 respondents. The sample data collection technique used is a questionnaire. The author distributed questionnaires to 100 JNE consumers in Lhokseumawe city. The distribution of questionnaires that have been carried out by the author gets the results of the study, namely, partially the product variable (X1), price variable (X2), location variable (X3), promotion variable (X4), people variable (X5), service delivery process variable (X6), and phsycal evidence variable (X7), has a positive and significant effect on the loyalty of JNE consumers in the city of Lhokseumawe, with the most dominant variable affecting the loyalty of JNE consumers in the city of Lhokseumawe, namely the phsycal evidence variable (X7). The simultaneous testing in this study results in that the product variable (X1), price variable (X2), location variable (X3), promotion variable (X4), people variable (X5), service delivery process variable (X6), and phsycal evidence variable (X7), have a positive and significant effect on customer loyalty at JNE delivery service company in Lhokseumawe city. Keywords: product, price, location, promotion, people, process, physical evidance, consumer loyalty